The long-read assembly of Apareiodon sp., a neotropical fish with a ZZ/ZW sex chromosome system - Wolf, Ivan Rodrigo [UNESP]; Schemberger, Michelle Orane; Azambuja, Matheus; de Oliveira, Fernanda Souza; Nogaroto, Viviane; Valente, Guilherme Targino [UNESP]; Martins, Cesar [UNESP]; Vicari, Marcelo Ricardo (FapUNIFESP (SciELO), 2024)
Neotropical fishes emerge as an extremely diverse group of vertebrates where genomic strategies to evaluate structural and functional features are still beginning. Here, we present a second draft genome of Apareiodon sp. (2n=54, ZZ/ ZW), adding PacBio technology whole genome sequencing, and assembling by combining two technologies (long and short reads). Using a detailed strategy for genome assembly with fish genomes of Pygocentrus nattereri, Carassius auratus, and Astyanax mexicanus as references, the final assembly of the Apareiodon sp. genome generated 93 scaffolds, an N50 of 37,200,078 bases, and a size estimate considering 28 scaffolds (26 autosomes+ZW) of ~945 Mb. In Apareiodon sp., this second genome draft confirmed that ~36% of the genome is composed of repetitive DNA. Furthermore, the new draft genome has improved genomic quality assessments, allowing the annotation of 36,290 genes and 15,683 proteins, which presented similarities to reference genomes. The second draft genome of Apareiodon sp. will be useful for research on integrative cytogenetic and genomic data. It will open perspectives for analyzing sex-determining genes in Neotropical fish with a ZZ/ZW sex chromosome system.
Keywords: Chromosomes; genome sequence; Parodontidae; Teleostei